Protein enriched breakfast meal from sweet potato and African yam bean mixes (Bangladesh Journal of Scientific and Industrial Research, 2019)
Protein malnutrition is common in the developing countries due to gross intake of foods high in carbohydrate and lipids. Fortification and diversification of food crops are key players in reducing protein malnutrition and the associated health risks. This research evaluated nutritional components of breakfast food obtained from mixes of Sweet potato (SP) and African yam bean (AYB). SP and AYB were pressure cooked using autoclave at 121oC for 10 and 60 minutes, respectively. Blends of SP and AYB at 100:0, 90:10, 85:15, 80:20, and 70:30 were used to produce a tasty and ready-to-eat breakfast food. Products were analyzed for proximate compositions. Physical and sensory attributes of the products were evaluated. Significant (p